Oral Transmission of Sexually Transmissable Infections: A Narrative Review - Queirós, Catarina (2019)
Over the last few decades, behavioral changes in sexual practices have made oral transmission of traditional sexually transmissible infections increasingly recognized. Patients harboring a sexually transmissible infection may first present lesions on the oral cavity, as these may be visible and interfere with basic functions such as speech or swallowing. Moreover, the oral cavity may function as a reservoir for future spread of these infections. In order to successfully control this problem, a greater focus on oral sex should be persued, along with promotion of the use of condom and education on safe oral sex practices. Furthermore, examination of the oral cavity should is essential when evaluating any patient suspected of harboring a sexually transmissible infection. In this article, oral transmission of several viral and bacterial infections is reviewed, including human papillomavirus infection, genital herpes, syphilis and gonorrhea, among others.